PENERAPAN TEKNIK SEO (SEARCH ENGINE OPTIMIZATION) PADA BLOG (STUDI KASUS: NOVA13.COM) - Cahyono, Nova Tri; Triyono, Joko; Raharjo, Suwanto (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
Websites on the internet is now very much and will continue to grow over time. To facilitate the search for websites on the internet, it needs a search engine. There are many types of search engines, but only one of the most popular and frequently visited, namely Google. The number of websites that have been indexed by Google is also very much, even in the millions. This will certainly lead to competition between the websites that have similar themes and discussions as well as having an almost similar keywords to snatch the top position of search results or SERP (Search Engine Result Page) on Google. With the SEO techniques applied, then the effort to get the best position in Google SERP will be easier. To implement the SEO techniques to blog with purpose to get the best position in Google SERP, first decide the targeted keywords and create a blog and set up the blog to make it more SEO Friendly, then implementation will use SEO methods SEO Onpage and SEO Offpage techniques to support performance. After making the implementation of these two methods will be tested on the Google SERP position blog for several days to know the progress of the SEO techniques. The results obtained that implemented SEO technique before the blog positions was on the second page of Google SERP, but after implementation SEO technique then slowly improved blog position and even be in the top five the first page of Google. It can be concluded that the implementation of proven SEO techniques went well.